Developmental Robustness: The Haltere Case in Drosophila - Giraud, Guillaume; Paul, Rachel; Duffraisse, Marilyne; Khan, Soumen; Shashidhara, L. S.; Merabet, Samir (Frontiers in Cell and Developmental Biology, 2021)
Developmental processes have to be robust but also flexible enough to respond to genetic and environmental variations. Different mechanisms have been described to explain the apparent antagonistic nature of developmental robustness and plasticity. Here, we present a “self-sufficient” molecular model to explain the development of a particular flight organ that is under the control of the Hox gene Ultrabithorax (Ubx) in the fruit fly Drosophila melanogaster. Our model is based on a candidate RNAi screen and additional genetic analyses that all converge to an autonomous and cofactor-independent mode of action for Ubx. We postulate that this self-sufficient molecular mechanism is possible due to an unusually high expression level of the Hox protein. We propose that high dosage could constitute a so far poorly investigated molecular strategy for allowing Hox proteins to both innovate and stabilize new forms during evolution.